L-Carnitine supplementation ameliorates serum tumor necrosis factor-alpha and matrix metalloproteinase-3 in knee osteoarthritis women (Bangladesh Journal of Pharmacology, 2017)
Seventy-two females with mild to moderate knee osteoarthritis were included in this randomized double-blind placebo-controlled study. Patients in the intervention group (n=36) received L-carnitine supplement (750 mg/day) for two months. L-Carnitine supplementation led to decrease in serum TNF-? and MMP-3 levels significantly in comparison with the baseline (p